Psychological Profile of Good and Bad Credit Payers in Barranquilla, Colombia - Navia-Núñez, Marcela (2024)
The financial world profits from the credit product, in turn, users can acquire goods that would otherwise be impossible for them. However, the circle is broken if one of the parties fails to comply, therefore, detecting possible bad payers in advance is important for companies. Research is done to discern personality traits of good and bad credit payers. First stage consists of in-depth interviews to ten analysts and credit users. It is found that bad payers tend to indulge in external elements, being ostentatious, impulsive, and short-term; good payers, instead, indulge in internal elements. Money is a shelter to good payers, while it becomes a satisfaction, an oppression even a treason to bad ones. There are two profiles for bad payers: indifferent and addicted. For second research stage, nine factors and 48 items, with a Likert scale, are tested on 100 people. Factor analysis reduces factors to five. Money and calm are factors that identify bad payers.